Facilitators of and Barriers to Advance Care Planning in Adult Congenital Heart Disease. (27th December 2012) - Greutmann, Matthias; Tobler, Daniel; Colman, Jack M.; Greutmann‐Yantiri, Mehtap; Librach, S. Lawrence; Kovacs, Adrienne H.
Abstract Background Most adults with congenital heart disease (CHD) are interested in discussing matters related to advance care planning (ACP) early in the disease course, yet few such conversations actually occur. We aimed to evaluate factors that impact these discussions between patients and adult CHD providers. Methods Two hundred adult CHD outpatients completed a survey that included factors that might impact ACP discussions with their doctors. In parallel, forty‐eight providers within the Canadian Adult Congenital Heart Network completed a similar online survey. Responses were compared between the groups. Results Most providers (85%) worried that they were unable to reliably estimate life expectancy and believed that patients were not ready for end‐of‐life discussions if their estimated life expectancies were beyond 5 years (63%) or beyond 10 years (79%). In contrast, only 24% of patients, independent of disease complexity, thought they were not ready to talk about ACP. Most providers (83%) reported that greater certainty about patients' prognoses would help them discuss ACP. Patients thought that such discussions were best facilitated when they had trust in their doctors (85%) and believed their doctors are good at taking care of patients with CHD (78%). Conclusion Despite the fact that challenges to prognostication exist, discussions about ACP should not be reserved for patients with a severely reduced life expectancy. Most patients want these discussions regardless of the complexity of their disease. The trusting and close patient–doctor relationship in adult CHD, often evolving over many years, may provide an excellent platform from which to initiate such discussions.